구글 검색어 통계를 활용한 국내 체조종목의 관심도 분석 - 윤지운(Jiwun Yoon) (한국체육측정평가학회지, 2019)
이 연구는 구글 검색어 통계를 활용한 국내 체조종목에 대한 관심도를 측정하는 것이 목적이다. 이를 위하여 구글트렌드를 자료수집의 도구로 하여 2004년부터 2019년 11월까지 체조에 대한 검색어 사용량을 조사하였다. 구글트렌드가 제공하는 검색지수는 최고 100점을 만점으로 한 상대점수이기 때문에 검색지수 간에 수치를 직접비교하는것은 의미가 없다. 따라서 이 연구에서는 Zhu(2006)가 소개한 회귀분석에 의한 척도동등화 방법을 적용하여 검색지수 간 비교가능 한 점수로 변환시켰다. 척도동등화를 통하여 2004년 1월 체조 검색어량 100점을 기준 값(reference value)으로 설정하였으며, MS-Excel과 SPSS 프로그램을 사용하여 평활법에 따른 가중이동평균 그래프및 중다회귀분석을 실시하였다. 연구결과는 다음과 같다: 체조종목의 관심도는 2012년 8월에 435점으로 최고로 나타났고, 2016년 리우올림픽 이후 관심도가 점차 낮아지고 있다. 체조종목에 대한 대중의 평균 관심도는 78.4점으로서 축구종목의 약 15%, 야구종목의 약 10% 수준이다. 체조선수 중 대중의 관심도가 가장 높은 선수는 손연재 선수였으며, 체조종목의 관심도 변화에 가장 크게 기여하는 선수는 양학선 선수였다. The purpose of this study is to measure the degree of interest in Korea gymnastics using Google search statistics. Using Google Trend as a tool for data collection, we investigated the usage of search terms for gymnastics from January 2004 to November 2019. Since the search index score provided by Google Trend is a relative score with a maximum score of 100, it is impossible to direct comparison between the score. In this study, therefore the equating method by the regression analysis introduced by Zhu (2006) was applied and converted into comparable scores. Through the equating method, we set the reference value for volume of searching gymnastics in January 2004 as 100 points. And MS-Excel and SPSS program were used to perform weighted moving average graph and multiple regression analysis. The results are as follows: The degree of interest in gymnastics events reached a maximum of 435 points in August 2012, which has been gradually decreasing since the 2016 Rio Olympics. The average degree of interest in gymnastics is 78.4 points, which corresponds to about 15% of soccer and about 10% of baseball. Among the gymnasts, Son Yeon-jae was the most interested in the public, and Yang Hak-sun was the most contributing player to the variance of interest in gymnastics. KCI Citation Count: 0